Acceleration of unstructured implicit low-order finite-element earthquake simulation using OpenACC on Pascal GPUs. (2019) - Yamaguchi, Takuma; Fujita, Kohei; Ichimura, Tsuyoshi; Hori, Muneo; Maddegedara, Lalith
We accelerate CPU-based unstructured implicit low-order finite-element simulations by porting to a GPU-CPU heterogeneous compute environment using OpenACC. We modified performance-sensitive parts of the code, such as sparse matrix-vector multiplication and MPI communication, so that computations would be suitable for GPUs. Other parts of the earthquake simulation code are ported by directly inserting OpenACC directives into the CPU code. This porting approach enables high performance with relatively low development costs. When comparing eight K computer nodes and eight NVIDIA Pascal P100 GPUs, we achieve 20.8 times speedup for the 3 × 3 block Jacobi preconditioned conjugate gradient finite-element solver. We show the effectiveness of the proposed method through many-case crust-deformation simulations and a large-scale computation using finite element model with 10 9 degrees-of-freedom on a GPU cluster.